2022
DOI: 10.1136/bmjopen-2021-057197
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and associated factors among healthcare professionals in Ethiopia during the COVID-19 pandemic: a cross-sectional study

Abstract: ObjectivesThe objective of the study was to assess psychological distress (depression, anxiety and stress) and associated factors among healthcare professionals working at the University of Gondar Comprehensive Specialized Hospital, Ethiopia.DesignInstitution-based cross-sectional study.SettingThis study was conducted at the University of Gondar Comprehensive Specialized Hospital.ParticipantsStudy participants were healthcare professionals from University of Gondar Comprehensive Specialized Hospital. They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
2
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
3
5
2
6
Order By: Relevance
“…The reason may be those with higher educational qualifications might be having more responsibilities during their duties. This is in line with previous studies conducted among health workers including pharmacists [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reason may be those with higher educational qualifications might be having more responsibilities during their duties. This is in line with previous studies conducted among health workers including pharmacists [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Te reason may be those with higher educational qualifcations might be having more responsibilities during their duties. Tis is in line with previous studies conducted among health workers including pharmacists [35,36]. However, a previous study among community pharmacists and pharmacy technicians in Spain did not show association between education and level of psychological distress [16].…”
Section: Discussionsupporting
confidence: 91%
“…The findings revealed that isolated or quarantined populations with higher education level were more apt to develop depression or anxiety symptoms in comparison with those with a high school education or less, which was in consistent with prior findings that higher education level was significantly related to psychological distress like depression and stress ( 60 , 61 ). It could be conceived that people possessing higher education are likely to bear more burden on work, family or academic tasks, which contributed to their vulnerability to the impact of COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…However, the proportion of depressive symptoms, in our study was higher when compared to various studies conducted in Ethiopia; Eka kotebe Hospital 23.5% (29), Dessie comprehensive specialized hospital 27.8% (30), Gurage zonal public hospitals 25.8% (31), Saudi Arabia 43.9% (32), Southern China public hospital 38% (33), Southern Ethiopia 50.1% (22) and Gondar comprehensive specialized Hospital 42.7% (23). This discrepancy could be the result of different study designs and instruments; for example, the study conducted in Gondar and China utilized a DASS-21, whereas this study used a PHQ-9.…”
Section: Discussioncontrasting
confidence: 70%
“…In eastern Ethiopia, the prevalence of minimal, mild, moderate, and severe depressive symptoms were 27.9%, 24.1%, 9.4%, and 1.1%, respectively (20). Another study in central Ethiopia (21), southern Ethiopia (22), and Gondar (23) reported highest prevalence of DD, 60.3%, 50.1%, and 42.7% respectively.…”
Section: Introductionmentioning
confidence: 99%